Macrodosing to microdosing with psychedelics: Clinical, social, and cultural perspectives - KAYPAK, AYŞE CEREN (My University, 2022)
To date, the clinical and scientific literature has best documented the effects of classical psychedelics, such as lysergic acid diethylamide (LSD), psilocybin, and dimethyltryptamine (DMT), in typical quantities most often associated with macrodosing. More recently, however, microdosing with psychedelics has emerged as a social trend and nascent therapeutic intervention. This variation in psychedelic practice refers to repeat, intermittent ingestion of less-than-macrodose amounts that do not cause the effects associated with full-blown \"trips\". Microdosing paves the road to incorporating psychedelic drugs into a daily routine while maintaining, or even improving, cognitive and mental function. Unlike macrodosing with psychedelics, the influence of microdosing remains mostly unexplored. And yet, despite the paucity of formal studies, many informal accounts propose that microdosing plays an important role as both a therapeutic intervention (e.g., in mental disorders) and enhancement tool (e.g., recreationally-to boost creativity, improve cognition, and drive personal growth). In response to this relatively new practice, we provide an integrative synthesis of the clinical, social, and cultural dimensions of microdosing. We describe some of the overarching context that explains why this practice is increasingly in vogue, unpack potential benefits and risks, and comment on sociocultural implications. In addition, this article considers the effects that macro- and microdoses have on behavior and psychopathology in light of their dosage characteristics and contexts of use.
Keywords: Sosyal ve Beşeri Bilimler; Antropoloji; Sağlık Bilimleri; Social Sciences and Humanities; Anthropology; Health Sciences; ANTROPOLOJİ; Sanat ve Beşeri Bilimler; Sanat ve Beşeri Bilimler (AHCI); Psikiyatri; Klinik Tıp (MED); ANTHROPOLOGY; ARTS & HUMANITIES; Arts & Humanities (AHCI); PSYCHIATRY; Clinical Medicine (MED); Psikiyatrik Ruh Sağlığı; Psikiyatri ve Ruh Sağlığı; Koruma; Sanat ve Beşeri Bilimler (çeşitli); Genel Sanat ve Beşeri Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Psychiatric Mental Health; Psychiatry and Mental Health; Conservation; Arts and Humanities (miscellaneous); General Arts and Humanities; Social Sciences & Humanities